2021
DOI: 10.1001/jamanetworkopen.2021.14180
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Survival and Patterns of Recurrence in Gastric Neuroendocrine Carcinoma, Mixed Adenoneuroendocrine Carcinoma, and Adenocarcinoma

Abstract: IMPORTANCE Gastric neuroendocrine carcinoma and mixed adenoneuroendocrine carcinoma are rare pathological types of gastric cancer, and there is a lack of multicenter studies comparing the prognosis and recurrence patterns of gastric neuroendocrine carcinoma, gastric mixed adenoneuroendocrine carcinoma, and gastric adenocarcinoma.OBJECTIVE To compare the differences in long-term survival and patterns of recurrence among gastric neuroendocrine carcinoma, gastric mixed adenoneuroendocrine carcinoma, and gastric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 32 publications
5
32
1
Order By: Relevance
“…Besides, recent studies indicated that poorly differential NENs had a good response to the chemotherapy, which might explain the better OS of patients with NENs [ 19 , 20 ]. Moreover, recent studies have reported that gastric NEC has unique clinicopathological features quite different from intestinal-type gastric cancer (IGC) and may have a superior survival to IGC in early-stage patients, indicating that NENs have better survival than other pathological types of cancers, like adenocarcinoma [ 21 , 22 ], which is consistent with our research.…”
Section: Discussionsupporting
confidence: 92%
“…Besides, recent studies indicated that poorly differential NENs had a good response to the chemotherapy, which might explain the better OS of patients with NENs [ 19 , 20 ]. Moreover, recent studies have reported that gastric NEC has unique clinicopathological features quite different from intestinal-type gastric cancer (IGC) and may have a superior survival to IGC in early-stage patients, indicating that NENs have better survival than other pathological types of cancers, like adenocarcinoma [ 21 , 22 ], which is consistent with our research.…”
Section: Discussionsupporting
confidence: 92%
“…A multicenter retrospective study included 503 patients with GNEC, 401 patients with MANEC and 2875 patients with gastric adenocarcinoma. After propensity score matching, the 5-year disease-free survival rates of GNEC and gastric adenocarcinoma were 47.6% vs 57.6%, respectively ( P < 0.001); the 5-year disease-free survival rates of MANEC and gastric adenocarcinoma were 51.1% and 57.8%, respectively ( P = 0.02)[ 26 ]. The high proportion of neuroendocrine components in MANEC often indicates poor prognosis[ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to these findings, in a recent study including 401 patients, the 5-year disease-free survival was 51.1%, which was significantly better than that of NEC (47,6%) and worse than that of adenocarcinoma (57,8%). Furthermore, in the same series, advanced stages and lymph node metastasis were independent risk factors related to distant recurrence[ 76 ].…”
Section: Organ-specific Clinicopathological Findingsmentioning
confidence: 99%